2015
DOI: 10.1093/ijnp/pyv135
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Receptors, Brain-Derived Neurotrophic Factor, Serotonin and Dopamine Neurotransmission are Associated with Interferon-Induced Depression

Abstract: Background:The role of inflammation in mood disorders has received increased attention. There is substantial evidence that cytokine therapies, such as interferon alpha (IFN-alpha), can induce depressive symptoms. Indeed, proinflammatory cytokines change brain function in several ways, such as altering neurotransmitters, the glucocorticoid axis, and apoptotic mechanisms. This study aimed to evaluate the impact on mood of initiating IFN-alpha and ribavirin treatment in a cohort of patients with chronic hepatitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 79 publications
2
24
1
1
Order By: Relevance
“…We also confirmed that fluoxetine treatment is able to attenuate pathological lesions in K5.Stat3C mice. Many studies have shown that there is an interaction between the 5-HT system and BDNF/TrkB signalling, 3 and this interaction is likely to be the mechanism by which BDNF affects depression or anxiety behaviours. 3,18 Therefore, it appears that fluoxetine ameliorated skin lesions through BDNF/TrkB signalling in K5.Stat3C mice, and this improvement is unlikely to be a consequence of an antiproliferative effect in this model of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also confirmed that fluoxetine treatment is able to attenuate pathological lesions in K5.Stat3C mice. Many studies have shown that there is an interaction between the 5-HT system and BDNF/TrkB signalling, 3 and this interaction is likely to be the mechanism by which BDNF affects depression or anxiety behaviours. 3,18 Therefore, it appears that fluoxetine ameliorated skin lesions through BDNF/TrkB signalling in K5.Stat3C mice, and this improvement is unlikely to be a consequence of an antiproliferative effect in this model of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been growing evidence to show that the brain-derived neurotrophic factor (BDNF)/TrKB pathway can modulate serotonin (5-hydroxytryptamine; 5-HT) and other neurotransmitters, and this pathway has been implicated in the pathophysiology and treatment of depression and anxiety. 3 Clinical data have also revealed epigenetic changes in the BDNF gene in adult male patients with anxiety and depression, 4 and increases in BDNF levels following treatment with fluoxetine, an antidepression drug. 4 Thus, increasing BDNF in the brain can be a potential therapeutic means for the treatment of psychocutaneous disorders, such as psoriasis, which accompany depression-and anxiety-like behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…74 In contrast, the COMT Val158Met rs4680 genotype oppositely altered the rs6295 association with interferon-induced depression. 75 Perhaps most intriguing is an interaction of the HTR1A rs6295 genotype with the phospholysine phosphohistidine inorganic pyrophosphate phosphatase (LHPP) gene in major depression, seen in Utah and Ashkenazi populations. Subsequently, LHPP was identified in a genome-wide association study of female melancholic depression 76 and a Mexican-American major depression cohort.…”
Section: Genetic Interactionsmentioning
confidence: 99%
“…[3][4][5][6] Cytokines activity is associated with: 1) significant alterations in diurnal HPA axis activity including the flattening of the adrenocorticotropin (ACTH) and cortisol diurnal fluctuations, and an increase in evening ACTH and cortisol concentrations 4 ; 2) increased activity of the metabolic enzyme indoleamine 2,3-dioxygenase responsible for degrading tryptophan to kynurenine which is then metabolized to quinolinic acid interfering with CNS activity 7 ; 3) decreased brainderived neurotrophic factor (BDNF) levels 8 , and 4) altered function of the glucocorticoid receptors. 9 The effect of IFN-α seems to be purely biological rather than psychological, but patients during an antiviral treatment are going through a difficult phase in their life caused by neuropsychiatric symptoms such as emotional lability, cognitive decline and insomnia, as well as somatic symptoms including fever, nausea, lack of appetite, and weakness. In vulnerable individuals, this stressful situation may cause depression.…”
Section: Introductionmentioning
confidence: 99%